2017
DOI: 10.17096/jiufd.35768
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Styloid Process Morphology and Calcification Types in Both Genders With Different Ages and Dental Status

Abstract: Purpose:The purpose of this study was to investigate the morphology and calcification pattern of the styloid process (SP) and to determine their relations with subjects’ age, gender, and dental status.Materials and Methods:910 panoramic radiographs were stratified by age, dental status and gender. The distance between the points where SP leaves the tympanic plate of the temporal bone and the bony tip of SP was measured. Calcification patterns were classified as : (A) Region 1, tympanohyal alone (B) Region 2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 30 publications
3
7
0
6
Order By: Relevance
“…Previous authors, similar to ours, reported the same prevalence rates in males and females [20]. A higher prevalence of calcification of this complex in patients between 20 to 40 years was in agreement with the results previously reported [21]; whereas, some researchers reported a higher prevalence in 50 to 59-years old [22].…”
Section: Discussionsupporting
confidence: 92%
“…Previous authors, similar to ours, reported the same prevalence rates in males and females [20]. A higher prevalence of calcification of this complex in patients between 20 to 40 years was in agreement with the results previously reported [21]; whereas, some researchers reported a higher prevalence in 50 to 59-years old [22].…”
Section: Discussionsupporting
confidence: 92%
“…These changes require treatment, and since the calcification of the carotid artery is silent, it may be reported after a routine examination. It is important to evaluate other signs and symptoms to confirm the diagnosis, and it is necessary to differentiate the atheroma of the carotid artery from calcifications, such as thyroid cartilage, calcified lymph nodes, sialolites and phlebolites [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…En el presente estudio donde se analizó un total de 347 radiografías, se encontró un total del 27% de calcificaciones del proceso estilohioideo, ya sea uni o bilateral, relacionado este al Síndrome de Eagle que se caracteriza por presentar sintomatología dolorosa (28)(29)(30)(31)(32). Los estudios indican que no hay relación entre el sexo y la calcificación del proceso estilohioideo, pero sería de mucho interés determinar si la etnia es un factor determinante de esta patología (6,33).…”
Section: Discussionunclassified
“…El ligamento estilohioideo empieza en el hueso temporal por delante del agujero estomastoideo, lugar por donde se extienen muchas estructuras neuromusculares importantes tales como la arteria carótida, vena yugular interna y nervios craneales. El tamaño normal oscila entre los 20-32mm, y su elongación, si supera los 30mm, puede estar asociada al síndrome (6).…”
Section: Introductionunclassified